Exploring New Risk Factors for Postpartum Hemorrhage: Time to Consider Gestational Age?. Issue 1 (23rd March 2022) - Reale, S.C.; Bateman, B.T.; Farber, M.K.
Abstract : ( Anesthesiology. 2021;134:832–834. doi: 10.1097/ALN:0000000000003775) All birthing centers are now required by the Joint Commission to assess postpartum hemorrhage risk before delivery. This predelivery assessment is critical to classify women as being low, medium, or high risk for hemorrhage. Identifying mothers who are at high risk for postpartum hemorrhage can help specialists including anesthesiology, obstetric, and nursing teams closely monitor the mother's delivery and recovery, prepare blood and medical equipment preventatively, and reduce maternal morbidity and mortality. Unfortunately, postpartum hemorrhage still occurs in women without recognized risk factors.